Contemporary gendered pathways into adulthood in South Korea. (December 2022) - Park, Jiae; Koropeckyj-Cox, Tanya
Abstract: The transition to adulthood has become increasingly uncertain and variable. Among South Koreans, this transition has become more de-standardized since 1990, reflecting the effects of long-term economic stagnation and persistent, traditional gender norms, but little is known about the variability in pathways to adulthood among recent cohorts. This study employs sequence analysis to examine early life course trajectories between the ages of 19 and 35 and assess gender and cohort differences for South Koreans born between 1970 and 1985 (N = 8647), using the Korean Labor and Income Panel Study (KLIPS, Wave 1–23). The main results show that pathways into adulthood have become more varied in the current socioeconomic and cultural contexts in South Korea, particularly for women compared to men. At the same time, new gender-specific pathways into adulthood have appeared, while the traditional, distinctly gendered breadwinner-homemaker trajectory has declined. Highlights: Sequence analysis shows a variety of pathways into adulthood among young South Koreans. Gender has had a significant role in structuring the early life course across cohorts. Women's pathways into adulthood have become less predictable and more varied over time compared to men's. Newer gendered pathways into adulthood have emerged and become widespread.